Vocal repertoire for the twenty-first century, Volume 2: Works written from 2000 onwards - Manning, Jane 1938-2021 (Oxford scholarship online, 2021)
An insightful and practical interpretive guide to contemporary repertoire assembled by celebrated soprano Jane Manning. This second volume of the two-volume set covers works composed from 2000 onwards